1. RESULTS OF MONITORING AND CARE OF PATIENTS IN THE RECOVERY PERIOD AFTER OVARIAN CANCER TREATMENT SURGERY AT THE INTENSIVE CARE UNIT OF K HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of follow-up, care for patients in the recovery period after ovarian cancer surgery and analyze some influencing factors.Subjects and Research Methods: The study described 200 patients after ovarian cancer surgery at the Intensive Care Department of K Hospital.Results: The average age of the study group was 55.24 ± 11.48, 79% of patients had BMI within normal limits, the proportion of patients with comorbidities was 25.5%, and 42.5% of patients had undergone surgery. only 2% of patients experience complications after surgery. Factors related to care outcomes included age, duration of surgery, complications during surgery, postoperative blood transfusion status, and time on ventilator after surgery with statistically significant differences (p< 0.05).Conclusion: After surgery, the patient was fully cared for in terms of respiration, perception, circulation, urine, drainage, discomfort, pain care and pain relief.
Keywords: ovarian cancer; ovarian cancer surgery; nursing care; resuscitation care